Effects of M/G Ratios of Sodium Alginate on Physicochemical Stability and Calcium Release Behavior of Pickering Emulsion Stabilized by Calcium Carbonate - Yang, Xiaotong; Sui, Haomin; Liang, Hongshan; Li, Jing; Li, Bin (Frontiers in Nutrition, 2022)
The gel properties of sodium alginate (SA) have been revealed to be strongly correlated with its ratio of D-mannuronate to L-guluronate (M/G ratio). Herein, we focused on SA with different M/G ratios to conduct an in-depth study on the effect of M/G ratio difference on physicochemical stability and calcium release behavior of Pickering emulsion stabilized by calcium carbonate (CaCO3). The oil phase was added to the aqueous phase prepared by SA with different M/G ratios (2.23, 0.89, 0.56) and CaCO3 for one-step shearing to obtain E1, E2 and E3 emulsions, respectively. The results of particle size, microstructure, long-term stability, rheological and microrheological properties of the emulsions showed that the E3 emulsion prepared by SA with a smaller M/G ratio had smaller particle size and remained in flow condition during long-term storage, while the E1 and E2 emulsions had gelation behavior and stronger viscoelasticity. Moreover, the emulsion as a liquid calcium supplement was not only convenient to swallow and met the body's calcium needs, but also controlled release of Ca2+. The calcium release of the emulsions in a simulated gastric environment demonstrated that the calcium release ratio increased with the decrease of SA concentration, the increase of M/G ratio and the decrease of oil phase volume.